Extracellular L-asparaginase productive potential of the Priestia megaterium strain GB911 from Khanh Hoa sea of Viet Nam - Phuong, Do Thi; Anh, Nguyen Mai; Nga, Nguyen Thi; Huyen, Vu Thi Thu; Cuc, Nguyen Thi; Phuong, Trieu Ha; Minh, Le Thi Hong; Thao, Do Thi (Vietnam Journal of Science and Technology, 2024)
Currently, L-asparaginase isolated from terrestrial microorganisms has been employed for anticancer industrial production. This enzyme has the function of inhibiting the growth of acute lymphoblastic leukemia, Hodgkin’s lymphomas and other cancers. In this study, for the first time, L-asparaginase (ASNase) productive capacity of forty marine bacteria originating from Khanh Hoa sea of Viet Nam was screened and reported. Among those, twenty eight isolates were clarified for their extracellular ASNase activity based on their ability to form a pink zone around colonies on asparagine agar plates. As a result, four strains GB910, GB911, GB976 and GB982 showed high secreted extracellular ASNase activity, ranging from 8.64 to 13.22 IU/mg. Among these four most potential strains, GB911 exhibited better enzyme production capacity and was subjected to taxonomy identification. According to the 16S rRNA gene sequence on the GenBank database, strain GB911 was identified as Priestia megaterium and registered in the GenBank database with accession number MW407014. The purified enzyme obtained from strain GB911 exhibited strong cytotoxic activity against five monolayer and suspension cancerous cell lines with IC50 values ranging from 39 mU/mL to 98 mU/mL. The strain could serve as a promising source for industrial production of ASNase for clinical chemotherapeutic treatment.